An explorative study on the role of Disability Advice Desks in providing information on livelihood opportunities for disabled youth in the Cape Metropole - Jordan, Cleone (Department of Health and Rehabilitation Sciences, 2017)
There is evidence that disability and poverty are closely linked (Mitra, Posarac& Vick, 2012) and in a South African context this has become more evident as unemployment remains high among youth with disabilities (Lorenzo & Murray Cramm, 2012). To address this problem and align with South Africa's legislation, empowerment strategies such as the Employment Equity Act (DoL, 1998), the Skills Development Amendment Act (DoL, 1998) and the Code of Good Practice (DoL, 1998), amongst others, were implemented to ensure that employment of people with disabilities were supported. Despite this, youth with disabilities who live in poverty found it difficult for various reasons to access information which could lead to livelihood opportunities. The literature in this study spoke about empowerment strategies but it also looked at the barriers disabled youth faced in accessing livelihood opportunities, such as the digital divide. If people with disabilities were to address other areas in their lives that were lacking, and could not, for example, access information via Internet Technology because of poverty, then alternative ways were necessary for them to access information. For this reason, it was essential that people had access to information if they were to have the capacity to exercise their other rights. The purpose of this study, was to explore the role of Disability Advice Desks (DADs) in providing information on livelihood opportunities for disabled youth in the Cape Metropole. The methodology used in the study was a qualitative explorative case study, which was based on an instrumental approach. The data collection methods were in-depth interviews, participant observation, document analysis and reflective journaling. The participants included persons with disabilities who were the service providers at the DAD as well as youth with disabilities who approached the DAD for information. Data analysis was done inductively across the different data sources to verify categories and themes until data saturation was reached. The researcher also discussed how the data was triangulated because of her direct interest in the subject. Given that the work was inherently interpretive, the biases, values and judgments of the researcher was explicitly acknowledged so that it could be taken into account in the data presentation (Creswell, 1994). Ethical issues have been considered throughout the course of the research. Two themes emerged in the findings, and three themes formed part of the discussion. The first was 'Building capacity for change' which focused on objective one: to describe the role and function of the DADs in assisting youth with disabilities in accessing information that facilitates in livelihood development. The second theme looked at 'The personal nature of the work' and focused on the experiences of the DAD service providers in assisting youth with disabilities. The third theme in the discussion was 'Wake up, stand up and do things'. This theme focused on the experiences of the disabled youth and identified the enablers and barriers that influenced them to access information on livelihood development opportunities. The conclusion provides recommendations made, which included 1. To create more awareness on the service that is provided through the DADs 2. Use existing networks to expand the DAD project 3. Emulate the NAP (see chapter one) by providing an integrated service to the disability community 4. Strengthen existing ties with stakeholders and community partners 5. An assessment of organisational capacity be undertaken to evaluate its human capital, material and financial resources to construct an organisational development plan 6. Integrate ICTs as a tool for communication and service delivery for the development of the DAD 7. Continuing professional development among the service providers with disabilities